Reconstructive Hermeneutics in African Christology - Gathogo, Julius (HTS teologiese studies, 2015)
The article sets out to demonstrate African reconstructive Christology as the seventhChristological trend in African Christianity. Considering that African theology is kerygmatically universal, but theologically provincial, the study shows that Christology in our contemporary Africa can be best understood by retracing it from the early Christologicalcontroversies through to the present times. Certainly, African Christology in the 21st century is dominated by calls for contextualisation, indigenisation, rebirth, inculturation,renewal, rejuvenation, renaissance and reconstruction. To this end, the article endeavours todemonstrate that Christ, the ideal reconstructionist, the one who broke the cultural codes of his time in order to reconstruct the society, is the relevant model to our contemporary world.The article draws its theoretical framework from the works of Jesse Mugambi, Kä Mana,and Wachege, amongst other proponents of reconstructive motif in African theology. In its methodology, the article first attempts to identify some early Christological developments through to the contemporary trends. It subsequently attempts a survey of the six Christologicaltrends of the 20th century; that is a Christological trend that commits itself to interpreting and adapting Christology to modern mentality and situation; Christologies geared exclusively to thehistorical Jesus; Christology that tends to uphold the Trinitarian theology; Christologies based on the proclaimed Christ and the historical Jesus; Asian Christologies of inculturation and liberation;and African Christologies of inculturation and liberation. Afterwards, it analyses Christological trends of the 21st century where a seventh dimension, African reconstructive Christology, has become the norm. In so doing, the article builds on the premise that the primary task of African Christology today is restoration.